PEMBUATAN BIOETANOL DARI NIRA AREN (Arenga pinnata Merr) MENGGUNAKAN Saccharomyces cerevisiae - Meilani M Manurung; Gusti Handayani; Netti Herlina (Talenta Publisher (Universitas Sumatera Utara), 2016)
Bioethanol was an alcohol substance which can be obtained by biomass fermentation process. The purpose of this study was to determine the effect of agitation and volume of starter on yield and concentration of bioethanol produced from palm juice (Arenga pinnata Merr). Catalyst used was Saccharomyces cerevisiae. Observed variables were agitation and volume of starter in anaerobic fermentation. The experiment started with preparation of a starter followed by fermentation process. The product obtained from distillation process at temperature of 88 °C. The results showed that the higher agitation speed and volume of starter, yield and concentration of bioethanol will be higher. The highest concentration and yield obtained on the condition at a agitation of 100 rpm and 35% starter amounted to 47.618% (v/v) and 48.1411%. If it exceed that point, the changes of agitation and the addition of starter did not increase the concentration and yield of ethanol produced.